Junie B., first grader. Aloha-ha-ha! - Park, Barbara; Brunkus, Denise (New York : Random House, 2006)
Excitable Junie B. Jones manages to find trouble both before and during a trip to Hawaii and records each incident in a photo journal given to her by her teacher.
380
Accelerated Reader AR
Keywords: Jones, Junie B. (Fictitious character) -- Juvenile fiction; Vacations -- Juvenile fiction; Photojournalism -- Juvenile fiction; Schools -- Juvenile fiction; Diaries -- Juvenile fiction; Hawaii -- Juvenile fiction